If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(n + 1) = 4(n + -1) Reorder the terms: 2(1 + n) = 4(n + -1) (1 * 2 + n * 2) = 4(n + -1) (2 + 2n) = 4(n + -1) Reorder the terms: 2 + 2n = 4(-1 + n) 2 + 2n = (-1 * 4 + n * 4) 2 + 2n = (-4 + 4n) Solving 2 + 2n = -4 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 2 + 2n + -4n = -4 + 4n + -4n Combine like terms: 2n + -4n = -2n 2 + -2n = -4 + 4n + -4n Combine like terms: 4n + -4n = 0 2 + -2n = -4 + 0 2 + -2n = -4 Add '-2' to each side of the equation. 2 + -2 + -2n = -4 + -2 Combine like terms: 2 + -2 = 0 0 + -2n = -4 + -2 -2n = -4 + -2 Combine like terms: -4 + -2 = -6 -2n = -6 Divide each side by '-2'. n = 3 Simplifying n = 3
| -w-12=-3w-22 | | -(x+1)=-2(x+10) | | 3(n-5)=2(n+2) | | 14/9x15/52x8/35 | | -1/100x+60 | | 14/9x15/52x88/35 | | 3x+23=12x+58 | | 4x-4=2x+9 | | (3x-1)/3=(2x+3)/4 | | 2(x+3)=x-1 | | 4.2z=4(.6z-1.2) | | -34+13x=-13x-34 | | -2/5x=1/5 | | 3y=-2x+12 | | 37=-2x+12 | | -8-(-21)= | | 2/3(4x-1)=3/4(2x-4) | | 8n-14=11n-5 | | -8-(-29)= | | 4n+7=6n+11 | | p+28=13 | | 2(e^6x-6)=12 | | 1/2(8-6h)=b | | 7x-10=5x+20 | | f(x)=-x^2+10x+5 | | 15x-18=8x+-16 | | 11q+8+q= | | 15c^2-33c-36=0 | | y=2.50x | | 1/3+8 | | 36-6x=3x+23 | | 82=3x+4 |